O que são memórias literárias e como elas se realizam na proposta da olimpíada de língua portuguesa? - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2017)
The study, which is part of the Group of Research and Intervention in Reading, Writing and Literature at the School - Lelit, Federal University of Western Pará - Ufopa, develops within the scope of the debate on the teaching of Portuguese language, and seeks to understand what Is the genre literary memories within the scope of the Portuguese Language Olympics taken to the classroom as a teaching proposal? And what contributions does this proposal with the literary memories genre bring to the teaching of Portuguese in school? Based on the objectives of the study, documentary research was adopted for the purpose of the study, from which perspective the corpus of texts for the investigation was constituted: a set of thirty eight finalist productions of literary memories of students who reached the last Stage of the PLO / 2014; In addition to two other documents of the Olympiad Collect ion of a theoretical-methodological nature: the notebook As I remember: guidelines for the production of texts, and the document Judging Commission: guidelines for the participant. From the analysis of the corpus of the research I try to verify which conception of literary memories the Olympiad proposes in its instructional materials and that conception objectively is realized in the texts of the students within the conditions of production in which they were developed.
Keywords: Memórias literárias; Ensino; Olimpíada de Língua Portuguesa; CNPQ::CIÊNCIAS HUMANAS; LEITURA E PRODUÇÃO DE TEXTO